The potential for developing sports tourism as a tourist attraction in Bhondula Village, Gorontalo Regency - Mantu, Nur Alim; Rahayu, Tandiyo; Setyawati, Heny (Journal of Physical Education and Sports, 2025)
Bhondula Village in Gorontalo Regency is known for its natural attractions such as waterfalls, clear rivers, and rafting activities. However, the development of its sports tourism potential is still not optimal. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) in the development of sports tourism as the main attraction in Bhondula Village. The method used is qualitative with a case study approach. Data collection techniques are carried out through observation, interviews, and documentation involving the Head of the Tourism Office, village government, tourism awareness groups (Pokdarwis), the community, and tourists. The results of the study indicate that this village has strong natural resources and supports outdoor sports tourism activities such as camping, swimming, climbing, and rafting. However, several weaknesses were found such as less than optimal promotion, limited infrastructure, and inadequate security aspects. Opportunities that can be utilized include the potential for economic growth, support from the village government, and active community participation. Threats faced include natural disasters and unpredictable weather conditions. In conclusion, Bhondula Village has great potential in the development of sports tourism. A consistent strategy for improving facilities, security and promotion is needed to optimize the tourist attraction.